IMPLEMENTASI BUDAYA MADRASAH DALAM PERSPEKTIF PENDIDIKAN KARAKTER - Khairul Ihsan Arif; Ansar Ansar; Muh Ardiansyah (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2022)
The aim of this research was to determine and describe implementation of madrasah culture in perspective of character education. The method used in this research was qualitative by using the type of phenomenology research. This research was conducted at Madrasah Negeri 3 Luwu. Sources of data in this research were the principal, curriculum coordinator and teachers of Madrasah Negeri 3 Luwu. Data collection techniques were observation, interviews, and documentation. Data analysis used data reduction, data presentation, and drawing conclusions. Validity check of the data using triangulation. The result showed that the values of character education is integrated various structural aspects. The use of structural functional elements in implementing character education is an effort to supervise and guide the development of madrasah culture, in this case related to the internalization of character education values for madrasah academicians, especially the students. The implementation of madrasah culture in the perspective of character education through cultural approach that includes the behaviour of madrasah academicians, traditions, habits and cultural symbols is corresponding with the vision, the mission, and the purpose of madrasah and suitable with the effort of madrasah to build positive culture the behaviour of madrasah academicians have been applied to the values of character education which are entrenched as a result of integration into daily activities and tradition of Madrasah academicians through habituation efforts. In addition, Madrasah culture in the perspective of character education is also found in the cultural result that becomes symbol in the form of building and classroom arrangements and uniforms.